1998
DOI: 10.1115/1.2888060
|View full text |Cite
|
Sign up to set email alerts
|

The “Porcupine”: A Novel High-Flux Absorber for Volumetric Solar Receivers

Abstract: A new Volumetric (Directly-Irradiated)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(29 citation statements)
references
References 14 publications
0
28
0
1
Order By: Relevance
“…Kribus et al [16] designed and demonstrated the operation of the multistage receiver under elevated temperatures, which divided the aperture into separate stages according to the irradiation distribution, to achieve high working temperature and thermal efficiency. Karni et al [17] designed a volumetric solar receiver, nicknamed Porcupine. They demonstrated the capability of the Porcupine to endure concentrated solar flux of up to 4 MW/m2 and producing exist working fluid temperatures of up to 940 o C. Reddy and Kumar [18] analyzed the heat transfer behaviour of the modified cavity receiver with cone, CPC and trumpet reflector.…”
Section: Introductionmentioning
confidence: 99%
“…Kribus et al [16] designed and demonstrated the operation of the multistage receiver under elevated temperatures, which divided the aperture into separate stages according to the irradiation distribution, to achieve high working temperature and thermal efficiency. Karni et al [17] designed a volumetric solar receiver, nicknamed Porcupine. They demonstrated the capability of the Porcupine to endure concentrated solar flux of up to 4 MW/m2 and producing exist working fluid temperatures of up to 940 o C. Reddy and Kumar [18] analyzed the heat transfer behaviour of the modified cavity receiver with cone, CPC and trumpet reflector.…”
Section: Introductionmentioning
confidence: 99%
“…For water/steam, molten salt or liquid metal get heat inside absorber tubes in two dimensions, and the heat transfer process between absorber and air takes place in the whole volume. Metal wire/mesh [2], porous ceramic [3] and porcupine ceramic tubes [4] have been tested. Until now, the maximum outlet air temperature is up to 1700 C [4].…”
Section: Introductionmentioning
confidence: 99%
“…Metal wire/mesh [2], porous ceramic [3] and porcupine ceramic tubes [4] have been tested. Until now, the maximum outlet air temperature is up to 1700 C [4]. The silicon carbide ceramic foams fabricated are highly versatile porous materials which are used primarily in catalysts support, molten metal filtration, hot gas filtration, and combustion, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Hischier et al [87] recommended that a minimisation of the cavity wall thickness in relation with its strength to withstand the operating pressures should be performed. Open volumetric receivers were described by Ávila-Marín [90] and Karni et al [91]. Karni et al [91] presented a "Porcupine" volumetric solar receiver and its ability to withstand a solar flux of up to about 4 MW/m 2 , while producing gas exit temperatures of up to 940 °C.…”
Section: Solar Receivermentioning
confidence: 99%
“…Open volumetric receivers were described by Ávila-Marín [90] and Karni et al [91]. Karni et al [91] presented a "Porcupine" volumetric solar receiver and its ability to withstand a solar flux of up to about 4 MW/m 2 , while producing gas exit temperatures of up to 940 °C. This receiver consists of an array of pinfins or elongated heat transfer elements, implanted in a base plate.…”
Section: Solar Receivermentioning
confidence: 99%